Tissue-targeted inorganic pyrophosphate hydrolysis in a fugu5 mutant reveals that excess inorganic pyrophosphate triggers developmental defects in a cell-autonomous manner - Gunji, Shizuka; Kawade, Kensuke; Tabeta, Hiromitsu; Horiguchi, Gorou; Oikawa, Akira; Asaoka, Mariko; Hirai, Masami Yokota; Tsukaya, Hirokazu; Ferjani, Ali (Frontiers in Plant Science, 2022)
The level of inorganic pyrophosphate (PPi) must be tightly regulated in all kingdoms for proper execution of cellular functions. In plants, the vacuolar proton pyrophosphatase (H+-PPase) has a pivotal role in PPi homeostasis. We previously demonstrated that excess cytosolic PPi in the H+-PPase loss-of-function fugu5 mutant inhibits gluconeogenesis from seed storage lipids, arrests cell division in cotyledonary palisade tissue, and triggers compensated cell enlargement (CCE). Moreover, PPi alters pavement cell (PC) shape, stomatal patterning, and functioning, supporting specific yet broad inhibitory effects of PPi on leaf morphogenesis. Whereas these developmental defects were totally rescued by expression of the yeast soluble pyrophosphatase IPP1, sucrose supply alone cancelled CCE in the palisade tissue but not the epidermal developmental defects. Hence, we postulated that the latter are likely triggered by excess PPi rather than a sucrose deficit. To formally test this hypothesis, we adopted a spatiotemporal approach by constructing and analyzing fugu5-1 PDF1pro::IPP1, fugu5-1 CLV1pro::IPP1, and fugu5-1 ICLpro::IPP1, whereby PPi was removed specifically from the epidermis, palisade tissue cells, or during the 4 days following seed imbibition, respectively. It is important to note that whereas PC defects in fugu5-1 PDF1pro::IPP1 were completely recovered, those in fugu5-1 CLV1pro::IPP1 were not. In addition, phenotypic analyses of fugu5-1 ICLpro::IPP1 lines demonstrated that immediate removal of PPi after seed imbibition markedly improved overall plant growth, abolished CCE, but only partially restored the epidermal developmental defects. Next, the impact of spatial and temporal removal of PPi was investigated by capillary electrophoresis time-of-flight mass spectrometry (CE-TOF MS). Our analysis revealed that metabolic profiles are differentially affected among all the above transgenic lines, and consistent with an axial role of central metabolism of gluconeogenesis in CCE. Taken together, this study provides a conceptual framework to unveil metabolic fluctuations within leaf tissues with high spatio-temporal resolution. Finally, our findings suggest that excess PPi exerts its inhibitory effect in planta in the early stages of seedling establishment in a tissue- and cell-autonomous manner.